Professional development of technology teachers: does their training meet their needs? - Gumbo, M. T. (University of the Free State, 2020)
The phenomenological study on which this article is based inquired into Grade 9 Technology teachers’ professional development through workshops on pedagogical content knowledge (PCK) as well as their training needs. The workshops took place in Nelspruit in Mpumalanga, South Africa. Data were gathered from two groups of teachers who attended the workshops on two different days, but who were trained in the same way and were subsequently conveniently selected to participate in the study. Semi-structured focus group interviews were conducted with these teachers and the workshop facilitator was also interviewed. The training manual was scrutinised, the facilitation of the workshops was observed and a follow-up visit was done at two schools where the workshop participants taught. The findings revealed that while the teachers felt that the workshops developed them, such training did not fully meet their needs or expand their PCK repertoires. This study will inform the Mathematics, Science and Technology Academy (MSTA), which is tasked with offering in-service training to subject teachers in the province, about whether the workshops meet the needs of the attendees, thereby possibly necessitating a review of the training.
Keywords: Teachers' needs; Pedagogical content knowledge; Teacher development; Technology; Workshops